Analytical Study of the Effect of Government Subsidies on the Production of Sugar Beet Crop in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aims to study the effect of government subsidy policies on the production of sugar beet crops, and determine the relative importance of each in determining the total differences of the production quantity variable for the period 1988-2017.The most important results of this research were that the policy of subsidizing the final product prices fundamentally affects the change in the quantity of sugar beet production and that agricultural lending policy is one of the factors that motivate the farmer's decision to produce the crop.However, there is a difference in the order of the relative importance of the effect of each of them in changing the quantity of sugar beet production, which are in order as follows: (the price of the crop in the previous year - agricultural loans).Besides, the interruption of government support for this crop led to the cessation of sugar beet cultivation and thus let to the halt of sugar factories' production, and to the government's tendency to import sugar and fodder, which caused a large depletion of the foreign exchange.